ANALISIS PENGARUH LOKASI DAN PELAYANAN TERHADAP MINAT NASABAH MENABUNG DI BANK SYARIAH INDONESIA (BSI) KCP. LUBUK SIKAPING, KAB. PASAMAN - Yunelsa Pertiwi Ritonga; Amsah Hendri Doni (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
Interest in saving is a desire that comes from the customer to use bank products/services or save money at the bank. Growing interest in saving is influenced by location and service factors. In this research, quantitative research methods were used with research instruments in the form of questionnaires or questionnaires with a research sample of 50 respondents, in this case limited to district customers. Pasaman, subdistrict. Rao, the sampling technique used in the research was saturated samples, and the type of data used was primary data. The population and sample used in this research are some BSI customers. The data analysis techniques used are validity and reliability testing, classical assumption testing, multiple linear regression and hypothesis testing with a significance level of 5%. The research results show that partially (t test) the Location variable (X1) has no effect on interest in saving at BSI KCP.Lubuk Suhuing with a sig-t value of 0.930 > 0.05. People have an interest in making transactions at BSI, but several things make customers less interested in making transactions at the bank, such as the influence of location, where the bank location is quite far from where people live because the remote location requires transportation and takes quite a long time. With the conclusion that the more strategic the location chosen to be a bank office, the more interest in saving will increase. The service variable (X2) has no effect on interest in saving with a sig-t value of 0.887 > 0.05. The service at BSI has provided good service, but due to the lack of HR services, customers feel lazy about making transactions at BSI. With the conclusion that the better customer service, the interest in saving will increase. Simultaneously, the f test shows that the variables Location (X1) and Service (X2), each simultaneously have no effect on interest in saving. This is proven by sig-f 0.988 > 0.05. With the conclusion that the more strategic the location and the better the service, the interest in saving will also increase